2005
DOI: 10.1007/s10450-005-6020-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nanoporous Ceria Containing Heteroatoms, With and Without a Matrix

Abstract: We have been interested in the synthesis and study of porous ceria, because of its importance in several catalytic applications, and notably in automobile exhaust catalysts. The mesoporosity of these solids is susceptible to changes in synthesis conditions such as pH and concentration of the cerium and other cations precursors used. The use of organic matrices to control pore production during synthesis, was also investigated. In this contribution we present results from the synthesis of mixed Mn(III/IV) ceriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These include the characteristic groups and their maxima in the spectra as well as relevant literature data. 2,33,[35][36][37][38][39][40][41][42] All spectra show a characteristic sharp peak at 1391 cm À1 which is characteristic 41,42 for CeO 2 but could be also attributed to the stretching mode of COO and Ce-O-C 36,37 or /Ce-O-H. 43 The Ce-O-C bonds were, presumably, formed when organic residues trapped within the pores interact with the ceria surface. Furthermore, when the length of the polar tail of the Triton-X surfactant increases the strength and the width of the broad band between 640 and 400 cm À1 decreases gradually, indicating differences in the Ce-O bond length between the solids obtained from the three different Triton-X reversed micelles.…”
Section: Ftir Studies Of the Ceo 2 Samplesmentioning
confidence: 99%
“…These include the characteristic groups and their maxima in the spectra as well as relevant literature data. 2,33,[35][36][37][38][39][40][41][42] All spectra show a characteristic sharp peak at 1391 cm À1 which is characteristic 41,42 for CeO 2 but could be also attributed to the stretching mode of COO and Ce-O-C 36,37 or /Ce-O-H. 43 The Ce-O-C bonds were, presumably, formed when organic residues trapped within the pores interact with the ceria surface. Furthermore, when the length of the polar tail of the Triton-X surfactant increases the strength and the width of the broad band between 640 and 400 cm À1 decreases gradually, indicating differences in the Ce-O bond length between the solids obtained from the three different Triton-X reversed micelles.…”
Section: Ftir Studies Of the Ceo 2 Samplesmentioning
confidence: 99%
“…The isotherms of the Pd/CeZr1-F and Pd/CeZr2-F samples were Type IV with H 2 hysteresis, which is characteristic of mesoporous materials [19]. For Pd/CeZr3-F, the isotherm was Type II with H3 hysteresis, suggesting the presence of ill-defined pseudo-mesopores [20]. The isotherm of Pd/CeZr3-A displayed the same characteristics as those of Pd/CeZr1-A and Pd/CeZr2-A, implying that rearrangement of the pore structure of Pd/CeZr3-F occurred during aging.…”
Section: Textural Propertiesmentioning
confidence: 94%
“…These porous metal oxide modifications include the synthesis of mixed ceria with transition metals [8] [9], mixed metal oxide phases with the use of different solvent systems [10] and the use of templates such as humic acid [11] and CTAB [12] [13]. The results of this previous work showed that the use of these modifications played an important role in the formation of the target products and improved their structural characteristics.…”
Section: Introductionmentioning
confidence: 99%